The Influence of Ethnoreligious Conflict Effect on Student's Learning Motivation in North Halmahera - Olivia Asih Blandina (Fakultas Keperawatan, Universitas Klabat, 2020)
The conflict in North Halmahera affects various aspects of community life there. This study aims to find out the influence of ethnoreligious conflict effect on student’s learning motivation in North Halmahera. The sample of this study were students in North Halmahera who was studying at the higher education level. Samples taken as many as 39 people based on a purposive sampling technique. The data were collected using two scales: trauma scale and learning motivation scale. The conclusion from the results of this study is that students from North Halmahera who experienced trauma have wrong learning motivation. This can be seen from the description of trauma measurements that give the results of most (56%) North Halmahera students who study in higher education are in the moderate trauma category, 23% are in the high trauma category, and 21% are in the very high trauma category. On learning motivation, the measurement description results as much as 44% are at a high category, 28% are in the medium category, 23% in the very high category, and 5% in the low category.